EFFECT OF RHIZOBACTERIA ON GROWTH AND PESTICIDE RESIDUE IN CABBAGE (Brassica oleracea var. capitata) - Milda Ernita; Fuji Tria Mariska; Zahanis; Ermawati (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
Rhizobacteria are a group of bacteria that can increase plant growth and bioremediation.This experiment aims to determine the interaction of rhizobacteria and NPK Mutiara ongrowth, yield, and pesticide residues in cabbage. The experiment was carried out onandosol soil with an altitude of ± 1450 mdpl and located in Jorong Padang Laweh, LembahGumanti District Solok Regency, West Sumatra. The experiment used a CompletelyRandomized Design (CRD) with three replications The treatment is type of rhizobacteria aswithout rhizobacteria, Bacillus sp., Stenotrophomonas maltophilia, and Stenotrophomonaspavanii. The data were analyzed by analysis of variance (ANOVA) based on the F test at5%. If there is a significant effect, it is continued with Duncan's multiple distance test(DNMRT) at a 5% confidence level. The results showed that the best of Bacillus spincreased vegetative growth, while the Bacillus sp S. maltophilia, and S. pavanii couldincrease cabbage production, reduce cabbage leaf spot disease and bothStenotrophomonas sp were able to reduce the content of pesticide residues in cabbage andin the soil.Keywords: Bacillus sp; S.maltophilia; S.pavanii; cabbage, residue pesticides